(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
The article illustrates the analyzes of the main character in the “Sakhibkiran” written by the Uzbek poet Abdullah Oripov. Oripov is one of the most prominent figures in modern Uzbek literature, and Sakhibkiran is one of his well-known works. The poem explores Timur’s historical significance, his achievements, and his complex character. Through this work, Oripov highlights the legacy of Timur, blending historical facts with poetic expression, while also reflecting on the themes of power, leadership, and ambition.